Morphology and morphometry of Lycaenid eggs (Lepidoptera: Lycaenidae) - Munguira, Miguel L.; Martín, José; García-Barros, Enrique; Shahbazian, Gayaneh; Cancela, Juan Pablo (Zootaxa, 2015)
A morphological study with the use of scanning electron microscope of 67 species of Iberian Lycaenidae is presented. The study covers all the genera present in the area and shows an extraordinary variation in chorionic characters that allows egg diagnosis for most species. A morphometric study showed that the eggs from the sample have sizes that are correlated with adult size, but some species showed larger egg size than expected. Species hibernating at the egg stage proved to have on average larger sizes than those overwintering at other stages, probably because this trait might be favourable to endure the adverse conditions taking place during the winter. A cladistic analysis was performed using morphologic and morphometric characters from the egg with the result of poor discriminant power. However, some formal taxonomic groups such as the genera Lycaena and Satyrium were supported by our analysis due to specific apomorphic characters.